2013
DOI: 10.1111/imig.12075
|View full text |Cite
|
Sign up to set email alerts
|

God Bless Our Children? The Role of Generation, Discrimination and Religious Context for Migrants in Europe

Abstract: This article deals with individual and contextual effects on the religiosity of first and second generation migrants in Europe. Noticing that little attention has been directed towards intergenerational transmission of religion in processes of integration, we argue for an intergenerational perspective on immigrant religiosity. Social integration theory is used to derive the hypothesis that second generation immigrants are less religious than the first generation. Perceived discrimination is introduced in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Nevertheless, the latter can hardly be regarded as a central dimension of religiosity as the influence of networks is not uniquely related to religion. The only negative aspect of religiosity is mentioned when (personal) religious behavior triggers experiences of discrimination (see also Van der Bracht et al, 2013). Wearing the headscarf is, for instance, related to social exclusion by peers from school and extracurricular activities.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Nevertheless, the latter can hardly be regarded as a central dimension of religiosity as the influence of networks is not uniquely related to religion. The only negative aspect of religiosity is mentioned when (personal) religious behavior triggers experiences of discrimination (see also Van der Bracht et al, 2013). Wearing the headscarf is, for instance, related to social exclusion by peers from school and extracurricular activities.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Research indicates that religion in Europe is a more salient factor for partner choice than colour or racial differences (Lucassen & Laarman 2009). That particularly Muslim migrants, such as those from Turkish, Moroccan and Algerian origin seem to experience a negative image in Belgium is in line with this claim (Van der Bracht, Van de Putte & Verhaeghe 2013). This is likely to limit the willingness to establish mixed marriages from the side of Belgian natives, as well as from migrants residing in Belgium.…”
Section: Migration History and Partner Migrationmentioning
confidence: 94%
“…Migrants, especially of non-European origin, are often disregarded, belittled, and even discriminated against (Van der Bracht, Van de Putte & Verhaeghe 2013;Vandezande, Phalet, & Swyngedouw 2011;Zeleza 2002). Equal group status may be the prevailing norm as governments install antidiscriminatory laws.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Although considerable disagreement remains concerning the terms integration and acculturation, a point of agreement is that both integration and acculturation are processes that 6 span different generations (Alba & Nee, 1997;Birman & Trickett, 2001). Indeed, previous research has demonstrated that migrants conform to attitudes and behaviours of the receiving society in an intergenerational process (Van der Bracht, Van de Putte & Verhaeghe, 2013;Maxwell, 2010). Therefore, we expect that migrant generation is a fourth form of change over time in levels of disapproval of homosexuality among migrants, whereby second generation migrants will have more positive attitudes on homosexuality.…”
mentioning
confidence: 88%
“…Previous research has indicated that social integration takes place at even more local levels than the national (Van der Bracht, Van de Putte and Verhaeghe 2013). Therefore, we assume that periodic changes in levels of disapproval of homosexuality take place within countries and therefore nest survey-years within survey-countries.…”
mentioning
confidence: 99%